The Effect of Using Sport Parachute for Developing Fast and Explosive Strength and 100m Sprint Achievement in Sprinters with Simple Mental Disability - Abdul Ameer, Eman; Selam, Karam (Journal of Physical Education, 2020)
The importance of the research lies in using various and suitable training aids for training athletes with simple disabilities especially in 100m sprints so as to develop their record. The research aimed at designing exercises using training aids ) parachute) as well as identifying its effect on developing fast and explosive strength as well as 100m sprint achievement. The researchers used the experimental method on (5) elite sprinters with simple mental disability to conclude that using the parachute developed fast and explosive strength and 100m sprinting achievement in the subjects under study. Finally, they recommended using varied exercises with resistance to suit the subjects.